2023
DOI: 10.1021/acs.chemmater.3c00676
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Interphase between Argyrodite-Based Solid Electrolytes and the Lithium Metal Anode─The Kinetics of Solid Electrolyte Interphase Growth

Luise M. Riegger,
Sophie Mittelsdorf,
Till Fuchs
et al.

Abstract: Argyrodite-based solid electrolytes (SEs) are promising candidates for application in solid-state batteries (SSBs) due to their high ionic conductivity and mechanical malleability. However, they are reduced by lithium and form interphases when they are in contact with a lithium metal anode, which are needed to construct cells with high energy density. If the interphase is electronically insulating, a so-called solid electrolyte interphase (SEI) is formed that can protect the solid electrolyte from further degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…The high-frequency feature is attributed to the bulk SE impedance, which does not change significantly over the course of the experiment. 64,65 At lower frequencies, the Nyquist plot before cycling approaches a vertical line indicating blocking electrode behavior in the unlithiated carbon, which is essentially acting as a current collector with high electronic conductivity and negligible Li activity (Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
“…The high-frequency feature is attributed to the bulk SE impedance, which does not change significantly over the course of the experiment. 64,65 At lower frequencies, the Nyquist plot before cycling approaches a vertical line indicating blocking electrode behavior in the unlithiated carbon, which is essentially acting as a current collector with high electronic conductivity and negligible Li activity (Fig. 5b).…”
Section: Resultsmentioning
confidence: 99%
“…We like to add that—according to classical solid state reaction kinetics with diffusion control—SEI formation should not come to an end at a certain time. However, it appears that finite SEI growth can be observed in some cases 55 . The reasons are yet not clear, and further work in the fine tuning of the SEI is required.…”
Section: Resultsmentioning
confidence: 99%
“…Argyrodite (Li 6 PS 5 X, X = Cl, Br) SEs possess both high ionic conductivity and relatively good interfacial compatibility against a lithium-metal anode compared with other sulfide SEs such as Li 10 GeP 2 S 12 and Li 3 PS 4 electrolytes. 15,16 However, in the composite cathode, both the cathode active material (CAM)/argyrodite SE and carbon/argyrodite SE interfaces are not thermodynamically stable. 10,17,18 Recent studies have demonstrated that inorganic coating layers such as LiNbO 3 (LNO), 19 Li 2 O–ZrO 2 (LZO), 20 and Li 1.175 Nb 0.645 Ti 0.4 O 3 (LNTO) 21 can suppress the degradation at the CAM/argyrodite SE interface.…”
Section: Introductionmentioning
confidence: 99%